Effectiveness of Ethanol Extract of Cloves (Syzygium aromaticum) in Inhibiting the Growth of Streptococcus pneumoniae - Dian Shavitri Ariani Rusmana; Rike Syahniar; Rina Nurbani; Muhammad Dwi Putra (Muhammadiyah Medical Journal, 2026)
Background: Pneumonia is a lung disease caused by Streptococcus pneumoniae. Streptococcus pneumoniae is the leading cause of death in children and the elderly. The content of clove flower ethanol extract shows bacteriostatic activity with a mechanism that damages bacterial cell walls. Eugenol content is known to play an important role in inhibiting the growth of S. pneumoniae. Purposes: This study aims to determine the effectiveness of ethanol extract of clove flowers (Syzygium aromaticum) in inhibiting the growth of Streptococcus pneumoniae. Methods: This research method uses an experimental method. The sample used was Streptococcus pneumoniae ATCC 49619. Ethanol extract of clove flowers that had been diluted with concentrations of 20%, 40%, 60%, 80% and 100% was tested for antibacterial properties using the Kirby-Bauer Agar Diffusion Test method in inhibiting Streptococcus pneumoniae. Results: The results of the antibacterial test of clove flower ethanol extract showed effectiveness in the form of an inhibition zone for the growth of Streptococcus pneumoniae with an optimal concentration of 80%, an inhibition zone size of 19.50 mm which is included in strong antibacterial, and there is a bioactive compound eugenol which is antibacterial. Conclusion: Ethanol extract of cloves (Syzygium aromaticum) has been effective in inhibiting the growth of Streptococcus pneumoniae.